Strategies to slow down the progression of myopia: A systematic review - Amila, Adelia Rizka; Azizi, Nurul Ainun; Rizky, Putri Sri; Nurhuda, M. Rizwan; Suryasna, Nogi; Rahman, Aldy; Andre, Dastin (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2025)
Globally, the prevalence of myopia or nearsightedness is rising quickly, which presents a serious public health concern. By 2030, approximately half of the world's population is expected to be impacted. Untreated nearsightedness can have serious health consequences, such as avoidable blindness and an estimated $244 billion in lost productivity worldwide each year. Serious difficulties might arise from untreated myopia, which frequently starts in childhood. Efforts to delay the progression of myopia have focused on the following three main intervention types: optical, pharmaceutical, and environmental. More investigation and methodical assessments are necessary to combat the expanding myopia epidemic. A systematic review was carried out in accordance with PRISMA criteria to evaluate existing strategies for slowing the progression of myopia. From the beginning to November 2024, a thorough search was carried out in ISRCTN, PubMed, ScienceDirect, and ClinicalTrials.gov, resulting in an analysis of 9833 articles, ultimately selected 16 RCTs involving 3,062 subjects. A standardized technique was used to evaluate the articles' quality after duplicate publications, review articles, and incomplete articles were eliminated. This study found that Soft Contact Lenses (SCL), Atropine (AT) eye drops, and Orthokeratology (OK) lenses are all useful for treating pediatric nearsightedness. SCL, especially bifocal varieties, slows the progression of myopia, although their usage may be restricted by pain and hygienic concerns. Despite its efficacy varying, low-dose AT (0.01%) also slows progression, and cautious dosing is necessary due to concerns about rebound effects when therapy ends. OK lenses considerably minimize axial elongation, particularly when used in conjunction with AT; however, there are concerns of infection and maintenance. The most successful treatments seem to be combination ones, such as OK lenses with AT, although they demand strict commitment. In conclusion, SCL, AT, and OK may be useful for slowing the progression of myopia.